Adult psychology - "Bischof,Ledford J." (London, 1976)
This second edition represents many changes. Approximately 80 percent of the text has been revised, rewritten, and organized, but more important are the changes in the field of adult developmental psychology. The explosion of interest and research predicted in the first edition has taken place. Where the first edition was primarily an annotated report on research using adult subjects, the second edition reflects a more organized approach, because adult developmental psychology has come of age in the past ten years.
Keywords: Psychology